2000
DOI: 10.3923/pjbs.2000.593.595
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Spacing and Potassium Levels on the Growth and Yield of Turmeric var. Sinduri

Abstract: An experiment was conducted during 1998-99 to study the effect of different spacing (50 cm x 20 cm, 50 x 30 cm and 50 x 40 cm) and K 2 O rate (0, 40, 75, 120 and 150 Kg haG 1 ) on the growth, dry matter, production and yield of turmeric (Curcuma longa L.). Close spacing produced the tallest plants (87.89 cm), medium spacing produced the plants (87.89 cm), medium spacing produced the plants with the highest finger breadth (6.95 cm) and primary finger per plant (2.71) while wide spacing produced with the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This confirms the findings of Shi et al (2016) that increasing plant density is a common technique for enhancing higher grain yield, as it increases the potential capacity of the crop canopy to capture solar radiation, water, and nutrients (Shi et al, 2016). This result is consistent with the results of Bahadur et al (2000) and Osunleti et al (2022) who observed significant increase in yield under closer spacing and attributed this to higher plant density per unit area of land.…”
Section: Resultssupporting
confidence: 88%
“…This confirms the findings of Shi et al (2016) that increasing plant density is a common technique for enhancing higher grain yield, as it increases the potential capacity of the crop canopy to capture solar radiation, water, and nutrients (Shi et al, 2016). This result is consistent with the results of Bahadur et al (2000) and Osunleti et al (2022) who observed significant increase in yield under closer spacing and attributed this to higher plant density per unit area of land.…”
Section: Resultssupporting
confidence: 88%
“…'Roma' is the only genotype used in our trial that has yields reported elsewhere in the literature. In previously published studies, fresh 'Roma' yields range 10.2-21.6 t•ha −1 [21][22][23], while we report yields of 27.9-57.2 t•ha −1 , excluding the outlying MARC 2020 'Roma' yield of 5.20 t•ha −1 .…”
Section: Discussionmentioning
confidence: 86%
“…One challenge in comparing our results with other published reports is the difference in plant spacing. Our wider spacing to account for mechanical planting and harvest results in a plant population of 22,222 plants•ha −1 compared to 50,000-164,300 [20][21][22][23][24] reported primarily from India where planting and harvest is by hand. Furthermore, it is important to note that the planting densities used in many of these studies are artificially high because they are calculated from small experimental plots and do not take into account space for walkways or aisles [22].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of [3] report, which observed that wider spacing (50 x 40 cm) generated the highest yield per plant (189.35 g).…”
Section: Yield Per Plant (G) Effect Of Spacingmentioning
confidence: 98%